Mental illness and suicide in British South Asian adults - Ineichen, Bernard (Mental health, religion & culture, 2012)
South Asians make up about 5% of the UK population. Their rates for mental illness and suicide have been shown by some researchers to be rather lower than that of the total UK population, using a variety of measures, and considering many psychiatric conditions. This paper reviews the literature on the extent of mental illness among British South Asian adults, and explores aspects of their service use, and their attitudes to mental illness. Some distinguishing features of British South Asian mental health are identified, including areas justifying further research. Variations in the South Asian population including generation, country of origin, religion, class, wealth and geography, emphasise the growing need to disaggregate this population when presenting data about them.